Solution NMR backbone assignment reveals interaction-free tumbling of human lineage-specific Olduvai protein domains - Issaian, Aaron; Schmitt, Lauren; Born, Alexandra; Nichols, Parker J.; Sikela, James; Hansen, Kirk; Vögeli, Beat; Henen, Morkos A. (Biomolecular NMR assignments, 2019)
Olduvai protein domains, encoded primarily by NBPF genes, have been linked to both human brain evolution and cognitive diseases such as autism and schizophrenia. There are six primary domains that comprise the Olduvai family: three conserved domains (CON1-3) and three human lineage-specific domains (HLS1-3), which typically occur as a triplet (HLS1, HLS2 and HLS3). Herein, we present the solution NMR assignment of the backbone chemical shifts of the separate HLS1, 2 and 3 domains of NBPF15. Our data suggest that there is no change in the structure of the separate domains when compared to the full-length triplet (HLS1–HLS2–HLS3). We also demonstrate that there is no direct interaction between the three domains.